What is the effectiveness of the negative pressure wound therapy (NPWT) in patients treated with open abdomen technique? A systematic review and meta-analysis. Issue 3 (September 2016) - Cirocchi, Roberto; Birindelli, Arianna; Biffl, Walter L.; Mutafchiyski, Ventsislav; Popivanov, Georgi; Chiara, Osvaldo; Tugnoli, Gregorio; Di Saverio, Salomone
Abstract : BACKGROUND: The open abdomen technique may be used in critically ill patients to manage abdominal injury, reduce the septic complications, and prevent the abdominal compartment syndrome. Many different techniques have been proposed and multiple studies have been conducted, but the best method of temporary abdominal closure has not been determined yet. Recently, new randomized and nonrandomized controlled trials have been published on this topic. We aimed to perform an up-to-date systematic review on the management of open abdomen, including the most recent published randomized and nonrandomized controlled trials, to compare negative pressure wound therapy (NPWT) with no NPWT and define if one technique has better outcomes than the other with regard to primary fascial closure, postoperative 30-day mortality and morbidity, enteroatmospheric fistulae, abdominal abscess, bleeding, and length of stay. METHODS: According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement and the Cochrane Handbook for Systematic Reviews of Interventions, an online literature research (until July 1, 2015) was performed on MEDLINE, PubMed, Cochrane Central Register of Controlled Trials, and Cochrane Library databases. The MeSH terms and free words used "vacuum assisted closure" "vac;", "open abdomen", "damage control surgery", and "temporary abdominal closure". No language restriction was made. RESULTS: The initial systematic literature search yielded 452 studies. After a careful assessment of the titles and of the full text was obtained, eight articles fulfilled inclusion criteria. We analyzed 1, 225 patients, of whom 723 (59%) underwent NPWT and 502 (41%) did not undergo NPWT, and performed four subgroups: VAC versus Bogota bag technique (two studies, 106 participants), VAC versus mesh-foil laparostomy (two studies, 159 participants), VAC versus laparostomy (adhesive impermeable with midline zip) (one study, 106 participants), and NPWT versus no NPWT techniques (three studies, 854 participants) in which it is not possible to perform an analysis of the different types of treatment. Comparing the NPWT group and the group without NPWT, there was no statistically significant difference in fascial closure (63.5% vs 69.5%; odds ratio [OR], 0.74; 95% confidence interval [CI], 0.27–2.06; p = 0.57), postoperative 30-day overall morbidity ( p = 0.19 ), postoperative enteroatmospheric fistulae rate (2.1% vs 5.8%; OR, 0.63; 95% CIs, 0.12–3.15; p = 0.57), in the postoperative bleeding rate (5.7% vs 14.9%; OR, 0.58; 95% CIs, 0.05–6.84; p = 0.87), and postoperative abdominal abscess rate (2.4% vs 5.6%; OR, 0.42; 95% CI, 0.13–1.34; p = 0.14). On the other hand, statistical significance was found between the NPWT group and the group without NPWT in the postoperative mortality rate (28.5% vs 41.4%; OR, 0.46; 95% CI, 0.23–0.91; p = 0.03) and in the length of stay in the intensive care unit (mean difference, −4.53; 95% CI, −5.46 to 3.60; p < 0.00001). CONCLUSION: The limitations of the present analysis might be related to the lack of randomized controlled trials, so there is a risk of selection bias favoring NPWT. For several outcomes, there were few studies, confidence intervals were wide, and inconsistency was high, suggesting that although there were no statistically significant differences between the groups, there was insufficient evidence to show that the outcomes were similar. We can conclude from the current available data that NPWT seems to be associated with a trend toward better outcomes compared to the use of no NPWT. It does reflect the evidence presented in the current systematic review; however, the data should be interpreted with substantial caution given a number of weaknesses (in particular, the lack of statistical significance and heterogeneity between studies, i.e., small sample size of the included studies, high variability between studies). We highlight the need for randomized controlled trials having homogeneous inclusion criteria to assess the use of NPWT for the management of open abdomen. LEVEL OF EVIDENCE: Systemic review/meta-analysis, level III. Abstract : Supplemental digital content is available in the text.